Spatial Characteristic of Coal Mining in Kutai Kartarnegara Regency, East Kalimantan Province - Nasruddin, Nasruddin (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Coal mining activities in Kutai Kartanegara Regency conducted in an open way. Number IUP announced by the Directorate General of Mineral and Coal, Ministry of Energy and the results reconciliation of Mineral Resources IUP with the 210 status Clean and Clear (C & C). The purpose of the study is to identify the characteristics and patterns of coal mining in Kutai Kartanegara Regency based landform units in order to see the distribution pattern of its spread. The method used the construct maps of landforms unit in Kutai Kartanegara Regency derived from Satellite Imagery Landsat 7 ETM + in 2012, A sheet of study area Indonesia Map, Geological Map, Soil type and field surveys Map using ArcGIS 9.3 facilities. The results showed that the characteristic of the coal mining in Kutai Kartanegara Regency is implemented by way of an open mining. With the status of the production details 151 IUP (72 %) and the exploration 59 IUP (28 %). Condition of the land of post coal mining in some areas showed low implementation of the rules set by the government for land reclamation, thus causing in high environment such as erosion, flooding and landslides. Unit landform with majority in the coal mining activities is wavy tectonic cluster. The cause of the pattern of coal mining activity tend to cause factors of the position / location of relatively shallow or have undergone a process of outcrops to the surface between 0-30 meters, easy access from the mine to the port. The research result recommendations is conducted anticipation program from the dangers of impact that occurs as erosion and sedimentation, water quality and soil (land potential), The licensing selection strictly refer to the legislation and in depth learning to identify a variety of potential post-mining land to be developed on the post-mining unit of the shape according to the character of the land